The feasibility of establishing a clothing retail store in Gumaca, Quezon - Nicdao, Justinne Santiago; Florendo, Racquel B. (1999.)
This study about the feasibility of establishing a clothing retail store in Gumaca, Quezon. The proposed site is one of the 40 municipalities of the province and the eight largest in terms of population. It was founded as a town 417 years ago and one of the oldest towns in Quezon. It is located 196 kilometers from Manila, to the south along the Maharlika highway at the crossroads of the route to the Bicol region and the Bondoc Peninsula. The general objective of the study is to determine whether it is feasible to establish a clothing retail store at the proposed location. Specifically, it aims to identify the target clientele, their clothing preferences and the cost they are willing to invest in clothing apparel. Further, it is aimed o estimate the capital requirements needed to put up the business nd how to finance them. The study focuses only on the conditions prevailing at present and will be true for the market concerned at a given period of time, However, this study is limited to the market feasibility that will determine id there is a potential market for ready-made clothing in the proposed location and how much capital it would entail to put up such business for operation. It includes market feasibility that will determine if there is a potential market for ready-made clothing in the proposed location and how much capital would it entail to put up such business for operation. It includes market survey to determine buying and clothing preferences of target clientele and actual estimates of costs related to capitalization from a research of prevailing prices in the market. The study is a field research and the descriptive method was used. As such, statistical tools used were the general measures of central tendency like the average, mean, mode, ratio and percentages. A survey questionnaire was the main instrument employed in gathering data. To supplement it, an ocular inspection of the location and personal interview of persons concerned were conducted for additional information. after the questionnaires were gathered, the responses were tallied, summarized and presented in tables for reference and analysis.There were 117 respondents out of a total of 120. a 97.5% return rate. Out of this, there were 59 males and 58 females. Majority (72%) of the respondents belonged in the 10-39 age range. The sampling method that has been employed was the purposive random sampling. Two days were spent in the location to distribute and retrieve questionnaires, conduct interviews and take pictures of the town's commercial center, specifically the market stalls and stores selling ready-made garments. The data were treated according to procedures. Each item in the questionnaire was coded to facilitate tallying. Then, through manual counting, the responses in each item were tallied. The tallied data were then assembled in statistical tables and graphs. For statistical analysis, mode, median, mean, ratio and proportion were used. The general results of the study concluded that there is an existing market for RTW's in the proposed location. The greater percentage of the town's population belongs to the age groups that have a great demand for clothing and the need to buy them. Further, the existing stores in town are not enough to answer the demand in ready-made garments of the population. A larger portion of the population buys clothing out of town. In addition, there is a general preference for ready-made clothing over the custom-made ones, thus, indication demand for the type of product the proposed project is planning to sell. Based on these findings, it can be gleaned that there is a room for another retail store that will sell ready-made clothing. Not only that there is a demand for these products but also, the size of the market is big based on the size of the population and the limited number of stores in town. As to capital requirement, the total cost estimate is Php 593,392.00. This amount will be financed through a three-year bank loan amounting to Php 200,000.00 and the rest through personal funds. In terms of the existence of a market and the availability of funds to finance the capitalization, the project to establish a clothing retail store in the proposed location is deemed feasible.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Stores, Retail -- Philippines -- Quezon Province